Representasi Visual Buku Biologi Pada Materi Sistem Sirkulasi - Melinia Maduratna; Ummi Nur Afinni Dwi Jayanti (BIOEDUSCIENCE, 2022)
Background: Representation is a tool to improve students' communication, interpreting, and problem-solving skills. Visual representation (RV) can provide information about understanding the object/phenomenon observed about the concept under study. This study aimed to determine the relationship between visual representations and material content and the relationship between visual representations and the reality of images contained in the Circulation System material. Methods: This study used a content analysis method with a qualitative data analysis technique. Results: The analysis results show a relationship compared to the category of significant relationships on the circulation system's material and the relationship of symbolic visual representations. Conclusions: The analysis that has been carried out on the visual representation of SMA/MA biology books in the city of Stabat for the circulation system material, it can be concluded that the Visual Representation relationship contained in SMA/MA biology books was found to be more dominant for the category of no relationship compared to the category of a significant relationship in circulation system material presented. In addition, when analyzed concerning the reality of the image, the visual representation displays the relationship of symbolic visual representations in the analyzed biology textbooks. In addition to choosing a textbook, the teacher should pay attention not only to the content of the learning material but also to look at the components in the book, one of which is the picture in the textbook. This will later be useful to support students' understanding of the concepts being taught.